ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DI UKM BATIK SEKAR JATI STAR DENGAN MENGGUNAKAN METODE ABC ANALYSIS DAN ECONOMIC ORDER QUANTITY (EOQ) - Jiroyah, Fakhma; Sumarsono (INVANTRI (Inovasi Dan Pengelolaan Industri), 2021)
SMEs of Batik "Sekar Jati Star" is one of the manufacturing industries engaged in batik making located in Jatipelem Village, Jombang and established since 1999. One of the typical motifs in ukm is jombangan motif that depicts the icon of Jombang city. The problem is management of raw material supplies is not optimal, where so far there is no evaluation and no inventory model method is used. So that the article aims to control the inventory of batik raw materials which include fabric, dye and wax. This inventory control includes the classification of each raw material for making batik using the ABC Analysis method. Next, determine the amount of economical raw material inventory using the Economic Order Quantity (EOQ) method. The results showed that the classification of raw materials using the ABC analysis method shows that the raw materials included in category A are fabric raw materials, category B is dye raw materials, and category C is wax raw materials. Implementation of the results of the classification of raw materials, so that the main priority of control is carried out according to the order of categories. The results of the EOQ inventory model show the monitoring of inventory control of raw materials for fabrics, dyes, wax for a year. Monitoring includes the time and quantity of economic Q, RoP, frequency of purchases, average inventory per week. Furthermore, from the comparison of inventory costs, the results of the EOQ model provide more economical results compared to the raw material inventory management that has been carried out so far for fabrics, dyes and waxes.